As emendas constitucionais n. 20/1998 e n. 41/2003 e o equilíbrio financeiro e atuarial nos regimes de previdência social - Ferraro, Suzani Andrade (2007)
The principal purpose of this dissertation is to investigate the relation between the Constitutional Amendments 20 and o 41 and the financial and atuarial balance and the Social Security. The secondary purpose of this dissertation is to demonstrate that the alterations imposed to Social Security by the Constitutional Amendments 20/98 and 41/2003 should respect the acquired rights of insured and servants, who, at the time of edition of said amendments, complied with the requirements necessary for retirement. The justification for the choice of the theme of this work is developed by reason of the serious doctrinaire and jurisprudential dissents on the extent and limits of Constitutional Amendments 20 and 41, the stone clauses, unfolded into acquired right and juridical safety of the public insured and servants. This work investigates, too, the constitutionality of said Constitutional Amendments in accordance with the fundamental principles inserted by the constituent assembly. Constitutional Amendments 20/1998 and 41/2003 modified the security concept itself, redefining untouchable juridical paradigms, such as, for instance, the juridical safety and acquired right statutes. The hypothese raised is the following: the rules that provide on the social security rights and guarantees are social to attain the nuclear problem of this dissertation, one started from analysis of the process of constitutionalization of Constitutional Amendments 20/1998 and 41/2003, in order to check whether such amendments are consistent with the will of the constituent assembly